PENERAPAN METODE SIMULASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS III SDN 1 TERBANGGI AGUNG - Wahyuni (AS-SALAM, 2017)
By studying, one can change behavioral behavior and can do things that previously could not be done. By studying, a person acquires certain skills of knowledge, skills and attitudes. Changes in behavioral levels occur as a result and learning process in students. This is called learning result. The involvement of teachers in various development activities in their schools and possibly on a wider level, especially to improve student learning outcomes. Science subjects in Class III SD Negeri I Terbanggi Agung, of course, experience sharing kenndala in the implementation to achieve the desired learning outcomes. One of the methods that can be used is by simulation method. With this method is expected to improve student learning outcomes as a whole.